Fat source effects on finishing steer digestion and metabolism - Bock, B.J.; Harmon, D.L.; Brandt, Robert T., Jr.; Schneider, J.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A replicated 3 x 3 Latin square design was used to explore the effects of fat source (none vs 3.5% soybean oil soapstock or animal tallow) when fed with high (1.0%) calcium on digestion and metabolism of a finishing diet by steers. Adding fat did not affect site or extent of starch or dry matter digestion. A net synthesis of long chain fatty acids occurred in the rumen. Feeding fat tended (P=.ll) to depress bacterial N flowing at the duodenum but did not affect nonbacterial N or total N.
Keywords: Beef; Digestibility; Fat; Calcium; Finishing